Public Expenditure and Financial Accountability Assessment of Baringo County, Kenya - World Bank (World Bank, Washington, DC, 2020)
The subnational Public Expenditure and Financial Accountability (PEFA) assessment seeks to ascertain the performance of the PFM system of county governments using the PEFA methodology. So far, the Government of Kenya has gained experience in the application of the PEFA methodology by undertaking four national PEFA assessments over the years, the latest of which was carried out in 2017 and the report is due for completion in 2018. However, this is the first subnational assessment to be carried out in Kenya following the adoption of a devolved system of government. It is notable that the national and subnational PEFA assessments are being done almost concurrently, and this is important because both levels of government share the same public finance management (PFM) system, implying that evidence-based reform agenda can be implemented simultaneously after areas of improvements are identified. The subnational assessments, which covered 6 out of 47 counties, have been jointly financed by the World Bank and International Development Research Centre (IDRC) through the Kenya Institute for Public Policy Research and Analysis (KIPPRA).